Development of a survey instrument to measure patient experience of integrated care - Walker, Kara Odom; Stewart, Anita L.; Grumbach, Kevin (BMC health services research, 2016)
Healthcare systems are working to move towards more integrated, patient-centered care. This study describes the development and testing of a multidimensional self-report measure of patients' experiences of integrated care. Random-digit-dial telephone survey in 2012 of 317 adults aged 40 years or older in the San Francisco region who had used healthcare at least twice in the past 12 months. One-time cross-sectional survey; psychometric evaluation to confirm dimensions and create multi-item scales. Survey data were analyzed using VARCLUS and confirmatory factor analysis and internal consistency reliability testing. Scales measuring five domains were confirmed: coordination within and between care teams, navigation (arranging appointments and visits), communication between specialist and primary care doctor, and communication between primary care doctor and specialist. Four of these demonstrated excellent internal consistency reliability. Mean scale scores indicated low levels of integration. These scales measuring integrated care capture meaningful domains of patients' experiences of health care. The low levels of care integration reported by patients in the study sample suggest that these types of measures should be considered in ongoing evaluations of health system performance and improvement. Further research should examine whether differences in patient experience of integrated care are associated with differences in the processes and outcomes of care received.